1995
DOI: 10.1111/j.1348-0421.1995.tb02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Red Blood Cell Instillation at Palatine Tonsil Effectively Induces Specific IgA Class Antibody in Saliva in Rabbits

Abstract: We have shown that the palatine tonsil effectively incorporates exogenous foreign substances instilled at its surface. It is not clear whether antigen‐specific IgA can be induced by the instillation. Sheep red blood cells (SRBC) were instilled at the palatine tonsil every three days as the antigen, and the agglutination titer of specific IgA in saliva was examined. Nasal or intragastric administration, which have been shown to induce specific antibody in saliva, were done as control experiments. Anti‐SRBC anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…These findings were in contrast to the findings of Fukuizumi and co-workers (Fukuizumi et al, 1995), who evaluated responses in rabbits that were immunized by the nasal vs. tonsil routes and found that IN immunization resulted in nasal responses, while IT immunization resulted in salivary responses. Human tonsillar immunization studies have evaluated the effect of antigen injection (Quiding-Jarbrink et al, 1995) rather than topical antigen application as evaluated here.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings were in contrast to the findings of Fukuizumi and co-workers (Fukuizumi et al, 1995), who evaluated responses in rabbits that were immunized by the nasal vs. tonsil routes and found that IN immunization resulted in nasal responses, while IT immunization resulted in salivary responses. Human tonsillar immunization studies have evaluated the effect of antigen injection (Quiding-Jarbrink et al, 1995) rather than topical antigen application as evaluated here.…”
Section: Discussioncontrasting
confidence: 99%
“…Subjects immunized by the tonsillar route had a higher number of specific antibody-secreting cells in removed tonsils than seen in subjects immunized by the other routes. These studies and others indicate that IgA-inductive sites (i.e., tonsils) of the common mucosal immune system (CMIS) may preferentially supply IgA-committed, antigen-sensitized cells to local mucosal regions (Brandtzaeg, 1984;Fukuizumi et al, 1995;Moldoveanu et al, 1995;Quiding-Jarbrink et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…immunization at the cellular level are being studied [12]. Although it was reported that injection of sheep red blood cells into palatine tonsils in rabbits induced an antibody-secreting cell (ASC) response in salivary glands (SG) [13], the cells involved in the induction of immune responses in NALT and their relation to the cells in the mucosal effector site are not clear. To obtain dissociated lymphocytes from the NALT will facilitate further studies of the cells involved and the interactions whereby mucosal immunoglobulin (Ig)A as well as circulating IgG antibody responses are induced and memory is established.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, we have been developing tonsillar application, a new immunization route for mucosal immunity, specifically for the oral cavity (3)(4)(5)(6)(7)13). Tonsillar application of sheep erythrocytes (4) and formalin-killed bacterial cells (7,13) induced production of salivary immunoglobulin A (IgA) and blood plasma IgG more effectively than did intragastric instillation or nasal application.…”
mentioning
confidence: 99%